The global spread of misinformation on spiders - Mammola Stefano; Malumbres-Olarte Jagoba; Arabesky Valeria; Alejandro Barrales-Alcalá Diego; Barrion-Dupo Aimee Lynn; Benamú Marco Antonio; Bird Tharina L.; Bogomolova Maria; Cardoso Pedro; Chatzaki Maria; Cheng Ren-Chung; Chu Tien-Ai; et al. (Cell Press, 2022)
In the internet era, the digital architecture that keeps us connected and informed may also amplify the spread of misinformation. This problem is gaining global attention, as evidence accumulates that misinformation may interfere with democratic processes and undermine collective responses to environmental and health crises. In an increasingly polluted information ecosystem, understanding the factors underlying the generation and spread of misinformation is becoming a pressing scientific and societal challenge. Here, we studied the global spread of (mis-)information on spiders using a high-resolution global database of online newspaper articles on spider–human interactions, covering stories of spider–human encounters and biting events published from 2010–2020. We found that 47% of articles contained errors and 43% were sensationalist. Moreover, we show that the flow of spider-related news occurs within a highly interconnected global network and provide evidence that sensationalism is a key factor underlying the spread of misinformation.